Year of the tiger - Higgins, Jack (Penquin Group, 1996)
Paul Chavasse was set for a quiet evening when he noticed the old women standing in the shadows opposite the house. The message from the past that she conveyed was to have dramatic and far reaching consequences, involving a daring adventure in Chinese-occupied Tibet